The Triassic Mesophlebiidae, a little closer to the crown of the Odonata (Insecta) than other 'triassolestids'. Issue 2 (2nd April 2020) - Tierney, Ayla; Deregnaucourt, Isabelle; Anderson, John M.; Tierney, Paul; Wappler, Torsten; Béthoux, Olivier
Abstract: Two new, subcomplete forewings belonging to the 'triassolestid assemblage', a group of Triassic stem-relatives of dragon- and damselflies (Odonata), are described. One, recovered from Australia (Aranbanga Volcanic Group), belongs to Mesophlebia antinodalis Tillyard, 1916, previously documented on the basis of two very incomplete wings. The other, recovered from South Africa (Molteno Formation), is assigned to a new species, Mesophlebia elegans sp. nov. The new data allow a reconsideration of the diagnosis of the genus Mesophlebia Tillyard, 1916 and a re-instatement of the family Mesophlebiidae Tillyard, 1916. Notably, the new specimens possess, near the wing base, a posterior lobe absent in most 'triassolestid' genera, but present in crown-Odonata and a number of their stem-relatives. Lobodonata tax. nov. is erected to accommodate odonates possessing this lobe. The nature of the 'vein-like' element anteriorly delimiting this lobe is discussed. We submit that it might have been initially composed of an invagination of the posterior wing-margin ('fibula'), which was later captured by AA, imposing its course on CuP. Ayla Tierney [ayla.tierney@qm.qld.gov.au ], Queensland Museum, PO Box 3300, South Brisbane BC, Queensland 4101, Australia; Isabelle Deregnaucourt [isabelle.deregnaucourt@edu.mnhn.fr ], Sorbonne Université, MNHN, CNRS, Centre de recherche sur la paléontologie – Paris (CR2P), 57 rue Cuvier, CP38, F-75005 Paris, France; John M. Anderson [jmanderson.gondwana@gmail.com ], Evolutionary Studies Institute, Witwatersrand University, 1 Jan Smuts Ave., Braamfontein, Johannesburg 2000, South Africa; Paul Tierney [paul.tierney@qm.qld.gov.au ], Queensland Museum, PO Box 3300, South Brisbane BC, Queensland 4101, Australia; Torsten Wappler [torsten.wappler@hlmd.de ], Hessisches Landesmuseum Darmstadt, Friedensplatz 1, 64283 Darmstadt, Germany; Olivier Béthoux [obethoux@mnhn.fr ], Sorbonne Université, MNHN, CNRS, Centre de recherche sur la paléontologie – Paris (CR2P), 57 rue Cuvier, CP38, F-75005 Paris, France.